Cost and time savings from a rapid access model of care using transient elastography to screen and triage patients with chronic Hepatitis C infection. (February 2014) - Whitty, Jennifer A.; Tallis, Caroline; Nguyen, Kim-Huong; Scuffham, Paul A.; Crosland, Paul; Hewson, Kaye; Pai Mangalore, Rehka; Black, Marrianne; Holtmann, Gerald
Abstract Background: Treatment uptake amongst patients with chronic Hepatitis C virus (HCV) in Australia is relatively low. New approaches to assessment have the potential to reduce public waiting lists, improve access to treatment, and to reduce healthcare costs. Aim: To describe the costs to the public hospital system and waiting time associated with a novel integrated rapid access to assessment and treatment (RAAT) model of care that utilizes Transient Elastography (TE) as a specialist outpatient-based approach for a streamlined assessment of patients with chronic HCV, compared to conventional outpatient management with liver biopsy (LB). Methods: Time from first medical review to treatment plan and costs associated with detection of fibrosis were recorded for patients receiving RAAT during a 3-month period, and for a similar historical cohort managed conventionally with LB. Costs related to medical and multidisciplinary team reviews and the TE/LB test itself were included. Results: Patients receiving RAAT had lower costs (n = 27, median AU$2716) and shorter time to treatment (median = 194 days) than for conventional management (n = 13, median $5005, 420 days; p < 0.01). Differences related to the lower TE test costs and the lower cost of consults between first medical review and establishment of a treatment plan. Conclusions: Based on real world audit data, this evaluation suggests TE, used as part of a new RAAT model of care, is cost saving to the health system in the short-term and reduces waiting times. The analysis reported here was intended to assess the costs related to detection of fibrosis, and is limited by the small sample size and potential selection bias. Future research should undertake a full economic evaluation at a whole of service level, to consider a more comprehensive and longer-term assessment of the costs and benefits associated with HCV management.